2021
DOI: 10.3390/ma15010183
|View full text |Cite
|
Sign up to set email alerts
|

Process Phenomena and Material Properties in Selective Laser Sintering of Polymers: A Review

Abstract: Selective laser sintering (SLS) is a powder bed fusion technology that uses a laser source to melt selected regions of a polymer powder bed based on 3D model data. Components with complex geometry are then obtained using a layer-by-layer strategy. This additive manufacturing technology is a very complex process in which various multiphysical phenomena and different mechanisms occur and greatly influence both the quality and performance of printed parts. This review describes the physical phenomena involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 125 publications
0
46
0
Order By: Relevance
“…In SLS, a laser beam melts the raw material, which is a powder form. The process has great ability to make end products for most industrial applications due to its build accuracy, high productivity for customized and complex-shaped things, and strong mechanical qualities [ 38 ]. For this reason, it has been used in several industrial and scientific fields, from prototypes to the fabrication of spare parts and small series in automotive and aerospace fields, to customized prostheses for biomedical applications [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In SLS, a laser beam melts the raw material, which is a powder form. The process has great ability to make end products for most industrial applications due to its build accuracy, high productivity for customized and complex-shaped things, and strong mechanical qualities [ 38 ]. For this reason, it has been used in several industrial and scientific fields, from prototypes to the fabrication of spare parts and small series in automotive and aerospace fields, to customized prostheses for biomedical applications [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fusion of the particles occurs on very short timescales in the order of seconds, which considerably limits the formation of entanglements, which follows the well-known reptation mechanism. Here, as the temperature of the bed is lower than the melting temperature of the polymeric material, diffusion is restrained by the molecular arrest of the polymer chains [ 65 ].…”
Section: Additive Manufacturing Techniques Used For Polymersmentioning
confidence: 99%
“…Gajera et al [113] identified laser power, scanning speed, layer thickness and hatch spacing as the most important process parameters in the DMLS manufacturing in terms of their effect on the mechanical and physical properties of built parts. Thomas et al [114] identified fifty key process parameters in SLM, clustered in the four categories of laser scanning parameters, material properties of the powder, powder bed and recoater parameters and built environment parameters.…”
Section: Manufacturing and Synthesis Of The Nano Compositementioning
confidence: 99%